Transport and deposition of heavy metals in the Ross Sea Region, Antarctica. Issue 20 (20th October 2015) - Tuohy, Andrea; Bertler, Nancy; Neff, Peter; Edwards, Ross; Emanuelsson, Daniel; Beers, Thomas; Mayewski, Paul
Abstract: Emissions and long‐range transport of toxic metals and metalloids pose a global threat to ecosystems and human health. Global industrialization occurring from the late nineteenth century releases large quantities of pollutants into the Earth's atmosphere. Despite international efforts to mitigate emissions, accumulation of metals is still observed in the most remote regions of the planet. New baseline studies are needed to determine (i) natural background concentration of pollutants, (ii) contributions of anthropogenic emissions, and (iii) potential remobilization of previously deposited metals. Constructing such records requires distinguishing source strength from transport efficiency to the recording site and accounting for local depositional effects. Here we investigate the sensitivity and representation of Southern Hemisphere atmospheric concentrations of heavy metals (Fe, Al, Mn, Pb, Tl, and As) in the Roosevelt Island Climate Evolution (RICE) ice core, a new coastal Antarctic ice core site. Concentration variability with precipitation is explored in daily surface snow samples collected over 70 days, while seasonal deposition is investigated through snow pit sampling. We find that snow sample concentrations increase with particular snow precipitation types (rime and fog) and enhanced meridional atmospheric transport to the site. Snow pit heavy metals peak in summer and also show variable intraannual peaks. Seasonal airmass modeling based on ERA Interim reanalysis data indicates a synoptic shift during the spring and summer months. We conclude that modern heavy metal concentrations are influenced by transport efficiency and scavenging behavior; and thus, time series records from RICE have the potential to provide representative data of regional changes in heavy metals. Key Points: Rime ice and fog contribute to heavy metal concentrations at coastal sites Long‐distance oceanic pathways deliver heavy metals to the Ross Sea Region